University internship systems and preparation of young people for world of work in the 4th industrial revolution - Oluyemi Theophilus Adeosun; Ayodele Ibrahim Shittu; Temitope J. Owolabi (Rajagiri Management Journal (RAMJ), 2022)
Purpose - As the 4th industrial revolution (4IR) unfolds, there is an increasing awareness that its implications for workforce transformation and shifts in workforce demand will profoundly impact the future of work. Specifically, the paper seeks to answer the following research questions: i) how does Students' Industrial Work Experience Scheme (SIWES) equip young people for the real world of work, especially in the era of the third industrial revolution?; ii) does SIWES support the exposure of young people to the world of digitalization?; and iii) what are the effects of the SIWES exposure on the employability of young people? This paper aims to evaluate the University Internship system and preparation of young people for the world of work in the 4th industrial revolution. Design/methodology/approach - This paper used a mixed method to unravel the objectives of this study, that is, quantitative and qualitative methods. For the former, structured questionnaires were used to elicit a response from 249 young people drawn from tertiary institutions across Lagos State, Nigeria. The latter used an in-depth interview method conducted among 45 respondents (25 employers of labor and 20 lecturers). Findings - The findings reveal that: SIWES contributes meaningfully to the advancement of knowledge and capacity building among young people; SIWES exposes young people to the world of digitalization, depending on the organization where the internship takes place; and SIWES pays little attention to financial rewards and more attention to the acquisition of skills that are relevant to the world of work. The practical and policy implications of the findings are critically discussed. Originality/value - This paper critically evaluates the SIWES policy amidst the growing threats of widening skills gap, greater inequality and broader polarization.
Keywords: 650; 4th industrial revolution; Graduates; SIWES; University internship systems; World of work